Tipo, stile, canone: appunti di terminologia paleografica - Crisci, Edoardo (Scrineum, 2020)
This contribution is a brief exposition about some terminological matters related to three terms commonly used in palaeography: type, style, canon. In order to define the semantic field of these terms and their paleographical euristic scope, the author analyzes their use, above all in the Greek context, but also in the Latin one, by re-reading a certain number of scientific contributions of the last decades. The result is a not univocal use, often unclear in its theoretical assumptions and ambivalent in its heuristic scope. The reflections developed on the problem suggest a certain prudence in the use of these terms and the need for a further theoretical study.